Micropropagation of Aegle marmelos L. — A Medicinal Tree through Culture of Axillary bud and Shoot tip Explants from In vitro Germinated Seedlings - Gandhi, K.; E. Rajesh; Saravanan, S.; Elamvaluthi, M. (International Journal of Scientific Research in Biological Sciences, 2018)
Aegle marmelos L. is an important medicinal tree and it is commonly known as bael tree. In the present study, an efficient and improved plant regeneration protocol was developed for A. marmelos. Axillary bud and shoot tips from the in vitro germinated seedlings of A. marmelos were used as explants. Murashige and Skoog (MS) medium used as basal medium and MS medium devoid of any growth regulators was used for the in vitro germination of seeds. MS medium supplemented with different concentration and combinations of growth regulators such as 6-benzyl aminopurine (BAP), indole-3- butyric acid (IBA) and α-naphthaleneacetic acid (NAA) were employed. The medium fortified with 11.11µM/L of BAP and 1.07µM/L of NAA was found to be effective one for the initiation and multiplication of shoots with highest mean number of shoots (24.20 ± 3.85) and maximum mean length of the shoots (6.02 ± 0.64). Half strength MS basal medium supplemented with 14.76 µM/L of IBA was found to be effective one for rapid and maximum root induction per micro shoot. The well rooted in vitro raised plants were successfully hardened house with survival rate of 80%. This effective and improved protocol may be useful for the large scale production of this plant.